The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1743-6109.2012.02819.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Patient Satisfaction, and Surgeon and Patient Trainer Assessment of the Coloplast Titan One Touch Release Three-Piece Inflatable Penile Prosthesis

Abstract: The Titan OTR represents an advance in penile prosthetic technology that is well accepted by patients and physicians. The study design allowed for realistic evaluation of the new technology aimed at enhancing clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…However, other studies which included such patients have uniformly found satisfaction rates of about 80-95% with the three-piece implant [6,10,[13][14][15][16][17][18]. In addition, patients' satisfaction with penile implants has been shown to be greater than for other ED treatments, with satisfaction rates of 91% for implants compared to 45% for PDE5 inhibitors and 36% for injection therapy in one study [18].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, other studies which included such patients have uniformly found satisfaction rates of about 80-95% with the three-piece implant [6,10,[13][14][15][16][17][18]. In addition, patients' satisfaction with penile implants has been shown to be greater than for other ED treatments, with satisfaction rates of 91% for implants compared to 45% for PDE5 inhibitors and 36% for injection therapy in one study [18].…”
Section: Discussionmentioning
confidence: 91%
“…In recent years, the introduction of local antibacterial measures with hydrophilic and/or antibiotic coated implants has lowered infection rates to about 3% [4,10]. Precautions during surgery, including washing and careful disinfection of the surgical area, as well as reduced traffic within the operating room, are likely to have contributed to the improvements.…”
Section: Discussionmentioning
confidence: 96%
“…It is estimated that over 50% of men between the ages of 40 and 70 suffer from ED to some degree 12. Over a decade ago, the introduction of phosphodiesterase-5 inhibitors (PDE-5 inhibitors) aided and substantially improved ED treatment 3. Despite its effectiveness being high and estimated at around 60%-70%,4 other more invasive therapies may still be required, such as alprostadil treatment via intraurethral route or intracavernous injections, and vacuum devices.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies published until now which evaluated each type of prosthesis independently as regards the satisfaction of the patient, the partner and the surgeon. Similarly, studies have been conducted to assess both types of prostheses independently in very specific scenarios such as to evaluate new developments and technical advances of each of the prostheses, or to compare their effectiveness in special clinical situations such as for concomitant DE and Peyronie's disease treatment 379101112…”
Section: Introductionmentioning
confidence: 99%
“…Ease of deflation was improved compared with historical data. 4 A Danish study revealed that 1 of 33 patients (3%) with an OTR pump implant had to undergo revision surgery for a deflation problem. 5 An 85% overall satisfaction rate was noted.…”
mentioning
confidence: 99%